Studying the Factors Effect on the Flowability of (ZnO – CuO/ Al2O3) Catalyst with Blending of Different Lubricants through Hopper - Mohammed, Malek M.; H. Radhi, Mazin A.; Nasir, Ali Yasseen (Al-Khwarizmi Engineering Journal, 2009)
One of the most important problems in tablet process is to control the flow of the catalyst through the hopper; Controlling the flow can be done either by changing the size of particles or added the different lubricant (stearic acid, starch, graphite) or blending of different lubricants. The study showed that we can control (increase or decrease) on the flow of the catalyst through the hopper by blending different lubricants for the constant percentage. The flow increasing when particles size (0.6 mm) and then decrease with or without lubricants, no effect on flow when particles size lower than (0.2 mm) with use that lubricants, and good flow on (0.4 mm) when use stearic acid and starch.